The Effect of Ease of Doing Business Indicators on Investment Interest: Empirical Evidence in DKI Jakarta Province - Martua, Aleknaek; Sayuti; Mulyana; Ginting, Irka Tia (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2023)
The development of a region is essentially inseparable from investment. Investment in general can help a region to encourage the economic growth needed to process the economic potential in the region. Until 2021, EoDB indicators need to be improved in supporting the investment climate. Until now, the EoDB is still considered a valuable reference for countries that want to measure the level of risk and cost of doing business. Provinsi DKI Jakarta in its current condition seeks to increase its investment amid the issue of moving the national capital. This research focuses on looking at the relationship between EoDB and investment interest in addition to other economic factors. The analysis method used in this study is to use PLS-SEM on a research sample of 150 entrepreneurs with medium and large business categories. This study proves empirically that the Ease of Doing Business Indicator in Provinsi DKI Jakarta has a significant influence on investment interest in Provinsi DKI Jakarta in addition to the Economic Factors used in the simultaneous equation model. In the Ease of Doing Business variable (X1), all indicators can significantly explain the Ease of Doing Business Indicator. A one unit increase in the ease of doing business indicator will potentially increase investment interest by 74.6% in Provinsi DKI Jakarta, ceteris paribus. The five indicators that explain the Ease of Doing Business Variable the most and their coefficients include Getting Electricity (0.806), Trading Across Border (0.761), Protecting Minority Investors (0.743), Getting Credit (0.728), and Registering Property (0.724).